Pengaruh Bauran Pemasaran Terhadap Penjualan Produk - Rohandi Rohandi; Aryati Arfah; Baharuddin Semmaila; Arifin Arifin (STIE AMKOP, 2022)
Abstract This study aims to explain the effect of the marketing mix (X), which consists of four variables, namely product, price, promotion, and distribution, on sales (Y). The population of this study was Telkomsel Card users in Palu City, with the sample determination method using the slovin method, and the number of samples studied was 98 respondents (people). The results of this research analysis using SPSS which can show the results of the F-test and t-test. The F test (simultaneous test) states that the independent variables (X) studied simultaneously have a significant influence on increasing sales of Telkomsel cards (Y) in Palu City. It is known that the F-count value is 13.403, meaning that F-count is greater than Ftable (13.403 > 2.47). This means that statistically, the variables of product, price, distribution, and promotion of Telkomsel Card products simultaneously significantly influence the increasing sales of Telkomsel Cards in Palu City. As for the t-test (partial test), it is known that the four variables, namely product, price, distribution, and promotion of Telkomsel Card products, have a significant effect on sales of Telkomsel Card products in Palu City. Keywords: Product; Price; Place; Promotion; Selling.